Pharmacokinetics of intravenous and intramuscular danofloxacin in red-eared slider turtles (Trachemys scripta elegans). - Corum, Orhan; Corum, Duygu Durna; Altan, Feray; Er, Ayse; Cetin, Gul; Uney, Kamil (The Japanese Society of Veterinary Science, 2018)
This study aimed to investigate the pharmacokinetics of danofloxacin in red-eared slider turtle (Trachemys scripta elegans) following a single intravenous (IV) and intramuscular (IM) administrations of 6 mg/kg, using a two-way crossover study with 30-day washout period. Eight clinically healthy red-eared slider turtle weighing 410-600 g (mean 490 g) were used for the study. Danofloxacin concentrations were measured using the reversed-phase high-performance liquid chromatography. The plasma concentration-time data were evaluated by a non-compartmental method. After IV administration, the elimination half-life (t1/2 ʎ z), mean residence time (MRT0-∞), area under the concentration-time curve (AUC0-∞), volume of distribution at steady state and total body clearance in plasma were 24.17 hr, 30.64 hr, 143.31 hr·μg/ml, 1.29 l/kg and 0.04 l/hr/kg, respectively. Following IM administration, t1/2ʎz, MRT0-∞AUC0-∞,peak concentration (Cmax), time to reach Cmax, and bioavailability in plasma were 32.00 hr, 41.15 hr, 198.23 hr·μg/ml, 8.75 μg/ml, 1.5 hr and 139.89%, respectively. Danofloxacin has clinically superior pharmacokinetic properties, including the complete IM absorption, slow elimination and wide volume of distribution in redeared slider turtles. However, further pharmacokinetics/pharmacodynamics studies are necessary for the treatment of diseases caused by susceptible bacteria with known minimum inhibitory concentration values in red-eared slider turtles.

PMID:30853667
Keywords: Pharmacology; Cross-Over Studies; Bioavailability; Red-eared slider turtles; Biological Availability; Danofloxacin; Injections, Intramuscular; Turtles; Anti-Infective Agents; red-eared slider turtles; Injections, Intravenous; danofloxacin; Animals; Pharmacokinetics; bioavailability; pharmacokinetics; Fluoroquinolones; 3. Good health